2019
DOI: 10.1021/acs.jpca.9b09310
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic Sulfuric Anhydrides

Abstract: Carboxylic acids react with sulfur trioxide to form carboxylic sulfuric anhydrides, RCOOSO 2 OH. In this article, new supersonic jet microwave spectra are presented for the anhydride derived from propiolic acid (HCCCOOH), and recent work on a series of carboxylic sulfuric anhydrides is reviewed. For the propiolic acid derivative, computed minimumenergy structures are reported for both the anhydride ( H C C C O O S O 2 O H ) a n d i t s p r e c u r s o r c o m p l e x (HCCCOOH−SO 3 ), and additional CCSD(T)/CBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The reaction of formaldehyde with formic acid is depicted in Figure , where the product P1 (H 2 C­(OH)­OCOH) is formed by the transition state TS1 after the prereactive complex C1. With regard to the reaction mechanism of HCHO + HCOOH, the hydrogen atom of the hydroxyl group in formic acid is transferred to the oxygen atom of the carbonyl group in formaldehyde, while the oxygen atom of the CO group in formic acid simultaneously adds to the central carbon atom of formaldehyde, leading to the formation of the carboxylic acid ester; this mechanism is similar to the reactions of sulfur trioxide with atmospheric acids. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The reaction of formaldehyde with formic acid is depicted in Figure , where the product P1 (H 2 C­(OH)­OCOH) is formed by the transition state TS1 after the prereactive complex C1. With regard to the reaction mechanism of HCHO + HCOOH, the hydrogen atom of the hydroxyl group in formic acid is transferred to the oxygen atom of the carbonyl group in formaldehyde, while the oxygen atom of the CO group in formic acid simultaneously adds to the central carbon atom of formaldehyde, leading to the formation of the carboxylic acid ester; this mechanism is similar to the reactions of sulfur trioxide with atmospheric acids. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the atmospheric concentration of SO 3 is appreciable at a high altitude (with low temperature), and the energy barriers of six studied reaction processes drop with the decrease of temperature as shown in Table S13. The equilibrium constants increase as the temperature decreases implying the significant atmospheric concentration of OSA and ODSA at a low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental research on the hydrolysis of sulfur trioxide (SO 3 ) catalyzed by formic acid has shown that formic acid can react with SO 3 forming sulfuric anhydride via introducing a new functional group −OSO 3 H barrierlessly . According to the statistical thermodynamic calculations, the estimated equilibrium concentration of carboxylic sulfuric anhydrides deriving from different original carboxylic acid is in the range from 10 3 to 10 7 molecules cm –3 . It is also found that −OSO 3 H has a stronger binding ability than the original −COOH resulting from more stable clusters involving carboxylic sulfuric anhydrides than those involving corresponding carboxylic acids through comparing the Gibbs free energy of formation and hydrogen bond energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in our laboratory has shown that carboxylic sulfuric anhydrides (CSAs) can be readily formed through a low-to-no barrier pericyclic reaction between a carboxylic acid (RCOOH) and SO 3 , viz., In cases where the R group of the carboxylic acid is a 3-fold rotor such as in acetic or trifluoroacetic acid (R = CH 3 , CF 3 ), the orientation of the rotor relative to the carboxyl moiety differs between that in the complex and that in the product. Thus, reaction for these species is accompanied by an additional 60° rotation of the R group.…”
Section: Introductionmentioning
confidence: 99%